Applications of Magnetite Nanoparticles in Cancer Immunotherapies: Present Hallmarks and Future Perspectives - Song, Qingle; Javid, Amaneh; Zhang, Guofang; Li, Yang (Frontiers in Immunology, 2021)
Current immuno-oncotherapeutic protocols that inhibit tumor immune evasion have demonstrated great clinical success. However, the therapeutic response is limited only to a percentage of patients, and the immune-related adverse events can compromise the therapeutic benefits. Therefore, improving cancer immunotherapeutic approaches that pursue high tumor suppression efficiency and low side effects turn out to be a clinical priority. Novel magnetite nanoparticles (MNPs) exhibit great potential for therapeutic and imaging applications by utilizing their properties of superparamagnetism, good biocompatibility, as well as the easy synthesis and modulation/functionalization. In particular, the MNPs can exert magnetic hyperthermia to induce immunogenic cell death of tumor cells for effective antigen release and presentation, and meanwhile polarize tumor-associated macrophages (TAMs) to M1 phenotype for improved tumor killing capability, thus enhancing the anti-tumor immune effects. Furthermore, immune checkpoint antibodies, immune-stimulating agents, or tumor-targeting agents can be decorated on MNPs, thereby improving their selectivity for the tumor or immune cells by the unique magnetic navigation capability of MNPs to promote the tumor killing immune therapeutics with fewer side effects. This mini-review summarizes the recent progress in MNP-based immuno-oncotherapies, including activation of macrophage, promotion of cytotoxic T lymphocyte (CTL) infiltration within tumors and modulation of immune checkpoint blockade, thus further supporting the applications of MNPs in clinical therapeutic protocols.